TRANSFORMATION AND IMPROVEMENT OF THE QUALITY OF ISLAMIC EDUCATION INSTITUTIONS IN BITUNG CITY - Ode Pade, La (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2022)
This study aims to describe the transformation and quality of Islamic education in Bitung City. This research method uses literature study. The results show that the transformation of Islamic education is urgently needed to improve its quality. In addition, Islamic education needs to improve its quality and must develop all the elements that support it as a characteristic of advanced educational institutions.